Japanese encephalitis virus: Biological clones from a clinical isolate quasispecies show differing neurovirulence in vitro and in a mouse model - Shu, Pin Yu; Kien, Chai Ong; Soon, Hao Tan; David, Perera; Kum, Thong Wong (2020)
The Japanese encephalitis virus (JEV), a leading cause of encephalitis, exists as quasispecies in clinical isolates. Using a limiting dilution method combined with immunohistochemistry to detect viral antigens, 10 biological clones were isolated and purified from a clinical JEV isolate (CNS138/9) derived from an autopsy brain. These biological clones were tested for neurovirulence in SK-N-MC and NIE-115 neuronal cells, and a 2-week-old, footpad-infected, JE mouse model. Nine clones were found to be neurovirulent; one clone neuroattenuated. Although further studies are needed to determine genotypic differences, if any, in these clones, the limiting dilution purification and neurovirulence testing methods described herein should be useful for phenotypic studies of quasispecies of neurotropic viruses in general, and JEV and other flaviviruses in particular.